تأثير دعم وتأييد الإدارة العليا على مرونة منظمات التعليم العالي - دراسة ميدانية على جامعة تشرين والأكاديمية العربية للعلوم والتكنولوجيا والنقل البحري- - طرابلسية, شيراز; فياض, سامر (Latakia University Journal - Economic and Legal Sciences Series, 2018)
يهدف هذا البحث إلى دراسة العلاقة بين دعم وتأييد الإدارة العليا والمرونة لمنظمات التعليم العالي, حيث تم توزيع استبانة على عينة عشوائية من الإدارة العليا في جامعة تشرين والأكاديمية العربية للعلوم والتكنولوجيا والنقل البحري بلغت(20) إداري, وتوزيع استبانة ثانية على عينة من العاملين العلميين في كل من الجامعتين بلغت(327) عامل. وخلصت الدراسة إلى أن منظمات التعليم العالي محل الدّراسة تطبق مبدأ دعم وتأييد الإدارة العليا بشكل جيد, وتحقق منظمات التعليم العالي محل الدّراسة المرونة بشكل مقبول, حيث تواكب مجمل التغيرات الحاصلة, ومن خلال الاعتماد على اختبار T لعينتين مستقلتين باستخدام برنامج SPSS, تم التوصل إلى وجود تأثير لدعم وتأييد الإدارة العليا كأحد أدوات إدارة الجودة الشاملة على المرونة كأحد أبعاد الميزة التنافسية لمنظمات التعليم العالي محل الدّراسة. The aim of this study was to study the relationship between support and support of senior management and flexibility of higher education organizations. A questionnaire was distributed to a random sample of senior management at Tishreen University, Arab Academy for Science and Technology, Maritime Transport (20), and a second questionnaire on a sample of scientific scientists Each of the two universities amounted to (327) workers. The study concluded that the higher education organizations under study apply the principle of supporting and supporting the senior management well, and the higher education organizations studied the flexibility in an acceptable manner, where all the changes took place, and by relying on the T test for two independent samples using the SPSS program, The impact of supporting and supporting senior management as one of the tools of TQM on flexibility as one of the dimensions of competitive advantage of higher education organizations under study.